Steam-generation cooking versus dry heat convection of beef roasts differing in connective tissue - L.J. Bowers; Michael E. Dikeman; Leigh W. Murray; Sally L. Stroda (Kansas Agricultural Experiment Station Research Reports, 2012)
Foodservice managers strive to control factors that affect yield, serving cost, and palatability of beef. Beef roasts are traditionally roasted at temperatures from 325°F to 350°F for both home and institutional use. Roasts relatively high in connective tissue cooked with moist heat generally are more tender than when cooked with dry heat. Roasts cooked to 150, 160, or 170°F could be expected to have cooking losses ranging from 20% to over 40%. The issue of cooking loss led Winston Industries to develop the CVap Cook and Hold Vapor Oven (Winston Industries, Louisville, KY). CVap technology controls evaporation by creating a moist environment, which creates an opposing vapor pressure that minimizes moisture loss and should improve cooking yields. The objectives of our research were to compare the effects of moist-heat cookery in a CVap oven and dry-heat cookery in a Blodgett forced-air convection oven on cooked yield, cooked color, tenderness, and sensory attributes of beef roasts differing in connective tissue content cooked to different endpoint temperatures.
Keywords: Cattlemen& #x27; s Day; 2012; Kansas Agricultural Experiment Station contribution; no. 12-231-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1065; Beef Cattle Research; 2012 is known as Cattlemen& #x27; s Day; Beef; Steam-generation cooking vs. dry heat convection; Roasts; Connective tissue